CLINICAL CHARACTERISTICS AND THE TREATMENT OUTCOME IN PATIENTS WITH ACUTE LYMPHOBLASTIC LEUKEMIA - Damnjanović, Ivana; Virijević, Marijana; Suvajdžić Vuković, Nada (Srpski medicinski časopis Lekarske komore, 2021)
Introduction: Acute lymphoblastic leukemia (ALL) is the malignant transformation and proliferation of lymphoid progenitor cells. The disease outcome is significantly influenced by cytogenetic and molecular characteristics, leukocyte levels, the percentage of blood and bone marrow blasts, infiltration of the CNS,and the modality of the applied therapy.Aim: Determining clinical, immunophenotypic, and cytogenetic characteristics of patients with ALL; ascertaining remission rates, the presence of resistant forms, the rates of relapse and overall survival (OS); determining prognostic factors for patient survival.Materials and methods: This five-year retrospective study included 74 patients. The study covered the period from November 2013 to October 2018. The influence of sex, age, immune subtype of ALL, leukocyte levels, percent of blood and bone marrow blasts, and cytotoxic-molecular characteristics on survival were analyzed.Results: A total of 56 (75.0%) patients had B-cell ALL, while 18 (25.0%) patients had T-cell ALL. The average age was 49.5 years (20 - 77). Complete remission was achieved in 54 (72.9%) patients, 40 (71.4%) B-cell ALL patients and 14 (77.7%) T-cell ALL patients. Refractory leukemia was confirmed in 7 (9.4%) ALL patients,5 (8.9%) B-cell ALL patients and 2 (11.1%) T-cell ALL patients. Mortality during induction was observed in 13 (17.56%) patients, 8 (14.2%) B-cell ALL patients and 5 (27.7%) T-cell ALL patients. Relapse occurred in 25 (46.3%) patients, 20 (47.5%) B-cell ALL patients and 5 (33.3%) T-cell ALL patients. Univariate analysis showedthat an unfavorable outcome was associated with age ≥50 years (p < 0.001), COP chemotherapy (p < 0.001), non-transplant patients (p = 0.011), and infiltration of the CNS (p < 0.001).Conclusion: Survival in ALL patients is significantly affected by patient age, modality of applied therapy, and infiltration of the CNS by disease.
Keywords: acute lymphoblastic leukemia; survival; prognostic factors